2021
DOI: 10.1021/acs.molpharmaceut.1c00460
|View full text |Cite
|
Sign up to set email alerts
|

68Ga- and 211At-Labeled RGD Peptides for Radiotheranostics with Multiradionuclides

Abstract: Probes for radiotheranostics could be produced by introducing radionuclides with similar chemical characteristics into the same precursors. We recently developed an 211At-labeled RGD peptide and a corresponding radioiodine-labeled RGD peptide. Both labeled peptides accumulated in large quantities in the tumor with similar biodistribution, demonstrating their usefulness for radiotheranostics. In this study, we hypothesized that probes for radiotheranostics combined with multiradionuclides, such as 68Ga and 211A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…In the meantime, the membrane-bound radioactivity [uptake × (1 – internalized ratio)] increased. Although the reason is not apparent, our previous report of radiolabeled RGD peptides showed similar results …”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…In the meantime, the membrane-bound radioactivity [uptake × (1 – internalized ratio)] increased. Although the reason is not apparent, our previous report of radiolabeled RGD peptides showed similar results …”
Section: Resultssupporting
confidence: 50%
“…Similarly, previous studies in our and other research groups reported a significantly reduced accumulation in normal tissues by blocking agents (RGD peptides). 28,33,34 The results of the blocking study confirm that [ 67 Ga]16 and [ 125 I]17 are reasonable as α v β 3 integrin-directed radiolabeled RGD peptides because the α v β 3 integrin also expresses on the microvessels of normal tissues, such as the liver and lung. 35 ■…”
Section: ■ Results and Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Thus, we synthesized and evaluated the 125/131 I-labeled di- 1) as a preliminary step for radiotheranostics with 211 At-labeled dimer RGD peptide. This is because the radiolabeling with radiohalogens such as 125/131 I and 211 At can be achieved using the same tributyltin precursors, and 125 I-and 211 At-labeled probes showed very similar biodistribution patterns in our previous studies [8,10,11]. Moreover, 125 I is commercially available and has a long half-life (t1/2 = 59.4 d), which is appropriate for fundamental research.…”
Section: Introductionmentioning
confidence: 74%
“…The binding affinity of 6 for α v β 3 integrin (IC 50 : 1.2 ± 0.5 nM) was higher than that of c[RGDf(4-I)K] (IC 50 : 23.2 ± 17.2 nM) [11]. It was reported that IC 50 values of dimeric RGD peptides in the α v β 3 integrin competitive binding assay were an order lower than those of original monomeric RGD peptides [16].…”
Section: Discussionmentioning
confidence: 95%